The Implementation of Restorative Justice for Juvenile Crimes Oriented Toward the Best Interests of the Child - Wikan Sinatrio Aji; Setya Wahyudi; Dwi Hapsari Retnaningrum; Muhammad Imam Akbar (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
Law enforcement treats children in conflict with the law as “small adults” who commit criminal acts. The handling of children as perpetrators of crimes punishable by imprisonment of 7 years or more frequently neglects the best interests of the child. This study examines whether the concept of Restorative Justice can complement the resolution of cases involving children in conflict with the law, particularly those facing a sentence of 7 years or more. This study uses a normative juridical research method. The research findings suggest that Restorative Justice can complement the resolution of cases involving children in conflict with the law, particularly those facing sentences of 7 years or more, as it fundamentally upholds children’s rights. Moreover, Restorative Justice can be applied to such cases through existing diversion mechanism, which shifts the legal process from criminal proceedings to non-criminal alternatives. This approach involves mediation and negotiation between the perpetrator, the victim, their families, the community, and law enforcement to identify the best solution for addressing the issues faced by children as criminal offenders.